Lead (Pb)-Resistant Bacteria Improve Brassica chinensis Biomass and Reduce Pb Concentration in Pb-Contaminated Soil - Pertiwi, Beauty Laras Setia; Ustiatik, Reni; Nuraini, Yulia (Journal of Tropical Biodiversity and Biotechnology, 2024)
Applications of inorganic fertilisers  and pesticides frequently increase lead (Pb) content in the soil and food crops. This study aims to isolate Pb-resistant bacteria and test the isolated bacteria in reducing Pb concentration and increasing biomass production of Brassica chinensis on Pb-contaminated soil.  Soil and plant samples were collected from agricultural land in Batu City, East Java, Indonesia. The isolated bacteria were tested for Pb resistance and then characterised  according to 16S rRNA Sequence. A pot trial with a completely randomised  block design consisting of 9 treatments and 3 replications was set to determine the effect of Pb-resistant bacteria inoculation on Pb residue, plant growth, and soil nutrients. The result showed that the isolated Pb-resistant bacteria were Bacillus wiedmannii and Bacillus altitudinis. The bacteria were resistant to Pb up to 10,000 mg/L PbNO3. Inoculation of the bacteria increased B. chinensis growth and biomass production, namely increasing the number of leaves (12%) and dry weight (35%).  Also, the bacteria reduced Pb residue in the soil by up to 88%. Moreover, soil essential nutrients such as total nitrogen, available phosphorus, and exchangeable potassium increased (12%, 73%, and 200%, respectively) after the application of Pb-resistant bacteria. The bacteria have the potential for bioremediation of Pb-contaminated soils on a large scale due to the bacteria prevent Pb uptake by food crops such as B. chinensis by reducing Pb content in the soil, which is good for food safety and environmental sustainability.